2011
DOI: 10.1142/s0217732311035328
|View full text |Cite
|
Sign up to set email alerts
|

Classical Mechanics of Many Particles Defined on Canonically Deformed Nonrelativistic Spacetime

Abstract: We provide the classical mechanics of many particles moving in canonically twistdeformed space-time. In particular, we consider two examples of such noncommutative systems -the set of N particles moving in gravitational field as well as the system of N interacting harmonic oscillators.1 For earlier studies see [39] and [40].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 45 publications
(91 reference statements)
3
33
0
Order By: Relevance
“…So, influence of features of space structures in the Planck scale on composite systems is less than this influence on elementary particles. In addition we have found that commutator for coordinates of the center-of-mass and coordinates of the relative motion is not equal to zero (19) because of noncommutativity (5). So, the motion of the center-of-mass depends on the relative motion in twist-deformed space.…”
Section: Resultsmentioning
confidence: 93%
“…So, influence of features of space structures in the Planck scale on composite systems is less than this influence on elementary particles. In addition we have found that commutator for coordinates of the center-of-mass and coordinates of the relative motion is not equal to zero (19) because of noncommutativity (5). So, the motion of the center-of-mass depends on the relative motion in twist-deformed space.…”
Section: Resultsmentioning
confidence: 93%
“…It should be also observed that such an extension (blind in A, B indecies) is compatible with canonical deformation (1). Precisely, in τ approaching infinity limit the space (9) with function f (t) = f ±,κ 1 t τ = κ 1 C 2 ± t τ passes into the well-known multiparticle canonical space-time proposed in [45] 4 (see also [46])…”
Section: Twisted N -Enlarged Newton-hooke Space-timesmentioning
confidence: 99%
“…and we can consider the motion of the center-of-mass independently of the relative motion. Taking into account (80) and (13)- (14), equations of motion for the center-of-mass of a body in gravitational field reaḋ…”
Section: Introductionmentioning
confidence: 99%